Implementasi System Kontrol Smart Room Menggunakan Perintah Bot Telegram Berbasis Internet of Things - Yossi Aristo Adu; Petrus Katemba (Ikatan Ahli Informatika Indonesia, 2023)
The development of internet technology at this time is speedy in various fields, so currently more and more people are using internet technology. One of the facts about the progress of Internet technology is the existence of the Internet of Things. This research focuses on how the Internet of Things can control lights and fans and monitor temperature remotely by utilizing the existing Telegram Bot application. Make it easier for users to control and monitor temperature, lights, and fans in the room by using the Telegram Bot indoors and outdoors. Users are connected to the internet using an Android smartphone to give commands to control lights and fans via telegram bots. NodeMCU ESP8266 must also be connected to the internet so that the whole system can run properly. for lights and fans to turn on or off. When the lights and fans comply with the command, the lights and fans will respond to the telegram bot via the telegram server, whether the lights and fans are on or off.